Feasibility Test Analysis on the UPT Humas UNS Information System - Dimas Tegar Zunanta; Endar Suprih Wihidayat; Puspanda Hatta (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2023)
The development of the UPT Humas UNS information system is carried out using the analysis, design, development, implementation, and evalution (ADDIE) methods. The evaluation technique used is black box testing involving two programming experts to assess the functional readiness of the information system. The feasibility test was carried out using two methods, namely the usability scale (SUS) system to determine the level of usability and the technology acceptance model (TAM) for acceptance analysis of the UNS Public Relations UPT information system. Based on the evaluation that has been carried out, the UNS Public Relations UPT information system that has been successfully developed can run functionally to serve the 12 existing services with a little record of improvement. Judging from the average SUS score obtained, which is 69.75, it is classified as good overall for the level of usability. For the results of the TAM analysis consisting of 6 TAM research hypotheses, the ease of using SI has a significant effect on the expediency and attitude in using SI. The expediency of SI has a significant effect on the attitude to use and the intention to use SI. The attitude to use SI has a significant effect on the intention to use SI and the intention to use SI has a significant effect on the actual use of the system.